Methods of Extracting Oil from Mechanical Mixtures - Bekjonov Rozisher Soatmurodovich; Rakhimboyev Norbek Ilkhom ugli; Akhmadjonov Azizbek Khayrullo ugli (Scientific Trends, 2024)
Oil and gas collection and preparation in the field is completed by sequentially changing the state of the products of the oil wells and separating them according to their individual composition and obtaining commodity raw materials. Thus, the technological process separates well products into two streams of raw materials: oil and gas. The technology of collecting, cleaning and using groundwater is considered separately as special processes. This process consists of three consecutive stages: separation; collect; bringing the oil and gas installed for commodity raw materials to their normalized properties. In the third stage, the oil stream is cleaned of formation water and mineral salts, and the hydrocarbons contained in it are separated to stabilize the oil, as a result of which the loss on the roads for sending the oil to processing is avoided. During this stage, hydrocarbons are separated from the gas streams (for degasification) and the product converted into gas and liquefied hydrocarbons. Thus, the third stage is the last stage of oil and gas collection - it is called oil and gas development stage. When oil and gas are processed, their chemical and physical properties change profoundly. Do not confuse recycling with such processing. The movement of oil and gas from measuring devices to their processing point (oil gathering point, gas processing plant) is called oil and gas gathering, and oil and gas transportation is called oil and gas transportation.
Keywords: Waterflooding, kerosene, field, product, high oil viscosity, carbonate reservoirs, geologic model.